1999
DOI: 10.1097/00003246-199910000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Admission cortisol and adrenocorticotrophic hormone levels in children with meningococcal disease: Evidence of adrenal insufficiency?

Abstract: Children with meningococcal disease have a wide range of initial plasma cortisol levels, with lower levels found in those who die. Many factors may affect cortisol levels, but adrenal insufficiency is probably uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 32 publications
2
54
1
4
Order By: Relevance
“…Two recent randomized controlled trials in adults on the use of steroids in suspected adrenal insufficiency showed conflicting results (12,13), further adding to the controversy. We identified only a few small observational studies (ranging from 13-72 patients; see Table E1 in the online supplement) examining adrenal insufficiency in pediatric critical illness (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). These pediatric studies used multiple different definitions for the diagnosis of adrenal insufficiency, focused almost exclusively on patients with septic shock (17,19,20,22,23), did not conduct corticotropin stimulation tests on all patients (only obtained random cortisol levels) (15,16,24), and used different doses for the corticotropin tests.…”
Section: Abstract Adrenal Gland; Adrenal Function; Adrenocorticotropimentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent randomized controlled trials in adults on the use of steroids in suspected adrenal insufficiency showed conflicting results (12,13), further adding to the controversy. We identified only a few small observational studies (ranging from 13-72 patients; see Table E1 in the online supplement) examining adrenal insufficiency in pediatric critical illness (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). These pediatric studies used multiple different definitions for the diagnosis of adrenal insufficiency, focused almost exclusively on patients with septic shock (17,19,20,22,23), did not conduct corticotropin stimulation tests on all patients (only obtained random cortisol levels) (15,16,24), and used different doses for the corticotropin tests.…”
Section: Abstract Adrenal Gland; Adrenal Function; Adrenocorticotropimentioning
confidence: 99%
“…Based on quoted estimates in the literature (14,(16)(17)(18)(20)(21)(22)(23), we assumed a prevalence of 40%; therefore, a sample size of 369 patients permitted an estimate of prevalence to within ± 5%, 19 times out of 20. To allow for a potential dropout rate of 5%, the total sample size was 389.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This case mimicked prolactinoma with ACTHoma, since the serum ACTH and cortisol levels were elevated due to meningitis at hospitalization. The serum ACTH titer can increase several fold under normal physiological conditions in response to stress, 11) with a 10-fold increase under intense stress such as during meningitis 9,10,13) or after surgery. 3,12) The serum ACTH titer at hospitalization in our patient was about 7-fold higher compared to the value after the meningitis was cured.…”
Section: Discussionmentioning
confidence: 99%
“…4,8) Meningitis is known to cause increases in the level of serum adrenocorticotropic hormone (ACTH), an adenohypophysial hormone, and the cortisol titer. 9,10,13) Here we describe a case of prolactinoma with a high serum ACTH level caused by meningitis.…”
Section: Introductionmentioning
confidence: 95%